Vertical Tax Externalities in the Theory of Fiscal Federalism - Keen, Michael (Washington, D.C. : International Monetary Fund, 1997)
Vertical tax externalities between levels of government can occur in federal structures, with responses to the tax policies of one level of government affecting the tax base of the other. Such effects mostly arise when federal and state governments co-occupy the same tax base. This paper examines these externalities by considering their implications for a range of issues in fiscal federalism: the relationship between state and federal tax rates, the equilibrium levels of these taxes, the relevance of experience in federal countries for policy design in international settings, intergovernmental grants, and the assignment of tax powers among levels of government.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet